Analisis Trend Dan Grafik Barber Johnson Pada Efisiensi Tempat Tidur Di Rumah Sakit X Kota Bandung - Rd. Sekar Putri Defiyanti; Sali Setiatin; Aris Susanto (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2021)
Trend analysis is a statistical analysis method used for planning and evaluating efforts to minimize risk for the better. The purpose of this study was to analyze trends and barber johnson charts on the efficiency of bed use at X Hospital, Bandung City. This type of research is a qualitative method with a descriptive approach. Observations and interviews were carried out with data processing officers and medical record reporting officers, while secondary data was obtained from RL3 Year 2020 at Hospital X Bandung City. Data analysis using least square trend method and Barber Johnson chart. The results showed that the trend of BOR and BTO in Quarter I-IV of 2020 decreased. The trend of AvLOS and TOI in Quarter I and II increased, while in Quarter III and IV it decreased. Based on the results of the study, it can be analyzed that the use of beds at Hospital X Bandung City in 2020 has not been efficient, only reaching 20-60% while the standard value according to Barber Johnson is 75-85%, but it can be predicted that the TOI indicator will be more efficient, while the BOR indicator , AvLOS, and BTO are increasingly inefficient because their values ​​are getting further away from the predetermined standard values. To increase efficiency in the use of beds, the hospital should evaluate the beds and improve the quality of service.